Enhanced Carboxymethylcellulose Sponge for Hemostasis and Wound Repair - Bi, Zhanjian; Teng, Haifeng; Li, Qiujing; Zhang, Shukun (Frontiers in Materials, 2022)
Skin is the interface between human and the outside world. After skin injury, bleeding control and wound protection is urgently needed. In the study, the carboxymethyl cellulose /carboxymethyl chitosan-polydopamine (CMC/CMCS-PDA) sponge is prepared for skin hemostasis and repair. The self-polymerization of dopamine (DA) and cross-linking between DA and CMCS are simultaneously completed by Michael addition reaction to form CMCS-PDA under alkaline condition. CMCS-PDA is introduced into CMC sponge by EDC/NHS to improve the hemostasis ability and wound repair. By increasing the dosage of CMCS to get CMC/CMCS-PDA1, CMC/CMCS-PDA2 and CMC/CMCS-PDA3 sponges, and the stability of CMC/CMCS-PDA sponge is improved with the increasing addition of CMCS. Compared with simple CMC/PDA sponge, CMC/CMCS-PDA sponge has high hemostatic effect for their dispersion stability and CMC/CMCS-PDA2 exhibits best hemostatic ability with proper crosslinking. At the same time, prepared CMC/CMCS-PDA sponge sponge has good antibacterial and antioxidant properties. Rat skin wound model showed that CMC/CMCS-PDA sponge can better promote wound repair. Therefore, CMC/CMCS-PDA sponge could be a potential wound dressing for skin hemostasis and repair.